As mulheres também são boas de bola: histórias de vida de jogadoras baianas (1970 - 1990) - Moraes, Enny Vieira (2012)
The thesis Soccer and gender in Bahia: permanent concerns (1970 - 1990) has the objective of telling and propagading the histories of footballers women in the hinterland of Bahia between the 1970s and 1990s, it aims to break down the silence and invisibility of them, aspects that are very usual in the history of Brazilian women's football. Oral history was the method used in the interviews with women who revealed their everyday sociability, their struggles, in short, their stories in the sport. These stories show that women's football in Bahia was expanding during the 80s. The hypothesis that guided this study was based on the notion that prejudice is a propeller of so many silencies. The testimony of the following women contributed to this research: Maria da Conceicao Araujo, Nara Rúbia Muniz Chaves Pinheiro, Maria Cruz Neide Sampaio, Jorge Sampaio Suely Ribeiro Morbek, Cleyde Regina Araujo, Neumanci Gonçalves Ferreira, Ferreira de Oliveira Ivonete Solange Santos and Bastos. Based on the investigations, this study discloses the stories of women players allowing to follow the path took by the women's football in Bahia. The history starts with the incipient babas in Jequié in the 70s until his alleged consolidation in the 80s, well represented by players from Feira de Santana, it also includes a part of the history of the Brazilian Women's Soccer team during the 90s, based on the interview of Solange S. Bastos. Based on contributions from studies in the areas of History, History of Physical Education and Gender has been possible to articulate stories of footballer women with issues such as prejudice, lack of infrastructure and credibility, issues that marked the history of the sport in the country. Soccer has been considered a space that celebrates virility and strength, male attributes, in such that it took lots of dedication and courage for women to get in this well kept places, places where female participation "should" allowed only in the stands. However, with the boldness and strength, they invade the lawns and keep on pushing to make soccer, in fact, a plural and democratic environment that represents a national history